The Influence of Perceived Quality and Perceived Risk on Interest in Buying Alfamidi Private Label Products - Nurid Dian Ikrimah; Sri Tjondro Winarno; Dita Atasa (Journal of Social Research, 2023)
A businessman or entrepreneur must be able to read the target market deeply and accurately to maximize sales volume because consumer perception is very influential on the continuity of the business or business and is very difficult to assess. Increased sales volume can greatly benefit from perception, especially if customer testimonials are included. Consumers will assess the quality and danger of private-label goods before making a purchase choice. Customers will choose to buy it if they believe their impression of its quality is high. Conversely, people will decide not to buy an item if they feel that the item has more harm than good. This study was conducted to know how much influence the perceived quality and perceived risk have on purchase intention in alfamidi private label products. The number of samples used was 50 respondents. The sampling technique used is non-probability sampling, with an incidental sampling method. Data collection using a questionnaire. The data analysis technique in this study was to use Partial Least Square with WrapPls 7.0 software. The results of this study indicate that: (a) perceived quality (X1) has a positive and significant effect on Purchase Intention (Y). (b) perceived risk (X2) has a negative and significant effect on Purchase Intention (Y).